Tales from a not-so-glam TV star / 7. - Russell, Nikki; Russell, Erin (Dork diaries, 2014)
"Nikki is in the spotlight. A reality TV crew will follow her and her friends for the whole month of March as they record their hit song together. But will the excitement also cause unexpected problems, now that cameras are everywhere Nikki and her friends go?"--Provided by publisher.